2022
DOI: 10.3390/nitrogen3040040
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Permafrost Thaw Removes Nitrogen Limitation and Rises the Potential for N2O Emissions

Abstract: Ice–rich Pleistocene permafrost deposits (Yedoma) store large amounts of nitrogen (N) and are susceptible to rapid thaw. In this study, we assess whether eroding Yedoma deposits are potential sources of N and gaseous carbon (C) losses. Therefore, we determined aerobic net ammonification and nitrification, as well as anaerobic production of nitrous oxide (N2O), carbon dioxide (CO2), and methane (CH4) in laboratory incubations. Samples were collected from non-vegetated and revegetated slump floor (SF) and thaw m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 84 publications
0
14
1
Order By: Relevance
“…Based on measured N 2 O emissions, N 2 O loss under optimal conditions may be 54.8 mg N 2 O-N m −2 per year, which is 0.14% of the initial inorganic N content of exposed Yedoma [87]. Marushchak et al [87] reported from bare, disturbed slump floor sites with high water content (WFPS ≥ 67%), but also undisturbed, dry sites (WFPS = 6-15%, mean of 13 ± 6) an N 2 O uptake [87] (Tables 1 and S2, Figure 5B) being in contrast to a study at the same site where even nonvegetated bare slump with intermediate water content (WFPS of 63%) had significant in situ N 2 O emissions (2.03 ± 1.39 mg N 2 O-N m −2 d −1 ) [256]. High N 2 O emissions on slump floor sites were detected only with measurable nitrate content (RTS Lena River [87]; Table S1).…”
Section: Gaseous N 2 O Loss and Based Microbial N Processescontrasting
confidence: 58%
See 4 more Smart Citations
“…Based on measured N 2 O emissions, N 2 O loss under optimal conditions may be 54.8 mg N 2 O-N m −2 per year, which is 0.14% of the initial inorganic N content of exposed Yedoma [87]. Marushchak et al [87] reported from bare, disturbed slump floor sites with high water content (WFPS ≥ 67%), but also undisturbed, dry sites (WFPS = 6-15%, mean of 13 ± 6) an N 2 O uptake [87] (Tables 1 and S2, Figure 5B) being in contrast to a study at the same site where even nonvegetated bare slump with intermediate water content (WFPS of 63%) had significant in situ N 2 O emissions (2.03 ± 1.39 mg N 2 O-N m −2 d −1 ) [256]. High N 2 O emissions on slump floor sites were detected only with measurable nitrate content (RTS Lena River [87]; Table S1).…”
Section: Gaseous N 2 O Loss and Based Microbial N Processescontrasting
confidence: 58%
“…Lower, similar, or higher rates of C mineralization and thus gaseous C released as CO 2 and CH 4 have been described at hillslope thermokarst landforms compared to undisturbed neighboring sites [88,257,276,277,286,287,297]. In comparison to undisturbed soils, soils in hillslope thermokarst landscapes are generally characterized by low C/N ratios and higher but highly variable inorganic N availability, dominated by ammonium, [29,87,125,213,256]. The increased inorganic N content is most likely due to the following: (1) thermo-erosion exposes mineral soils and thaws permafrost subsoil layers, which typically contain higher con-centrations of inorganic nitrogen (mainly ammonium) than topsoils [28,42,77,103,117,213], (2) physical mixing increases aeration and drainage, which promotes aerobic N mineralization [186,208,213], (3) reduced or absent uptake of plant nutrients due to disturbed vegetation.…”
Section: And N Mineralization and Inorganic Nmentioning
confidence: 93%
See 3 more Smart Citations